1999
DOI: 10.1063/1.480242
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity dependence and solvent effects in the photoisomerization of cis-stilbene: Insight from a molecular dynamics study with an ab initio potential-energy function

Abstract: Isomerization of trans-stilbene: Theory for pressure dependence of the rate J. Chem. Phys. 108, 9186 (1998); 10.1063/1.476365 Molecular dynamics simulation with an ab initio potential energy function and finite element interpolation: The photoisomerization of cis-stilbene in solution Molecular-dynamics simulations of the photoisomerization of cis-stilbene in supercritical argon were performed. The stilbene molecule is represented by ab initio quantum chemistry, while the solvent, the interaction with solvent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…9 The most intriguing result, besides the one that the rate of isomerization is independent of solvent in the first 40 ps, in contrast to experiment, 10 is that the excited trans and gauche minimum (the latter is obtained in the course of geometry optimization starting from the cis side) are separated by a barrier which corresponds to the so-called perpendicular stilbene. In other words, the S 1 minimum at 90°, if it exists at all, should originate from another singlet state.…”
Section: Resultsmentioning
confidence: 72%
“…9 The most intriguing result, besides the one that the rate of isomerization is independent of solvent in the first 40 ps, in contrast to experiment, 10 is that the excited trans and gauche minimum (the latter is obtained in the course of geometry optimization starting from the cis side) are separated by a barrier which corresponds to the so-called perpendicular stilbene. In other words, the S 1 minimum at 90°, if it exists at all, should originate from another singlet state.…”
Section: Resultsmentioning
confidence: 72%
“…Various models and approximate approaches have, of course, already been employed in dynamical simulations of the photoisomerization of cis-stilbene [7,21,[24][25][26][27][28]. Examples include the quasiclassical molecular dynamics approach of Frederick and coworkers [24][25][26] and the ab initio potential energy surface approach of van Gunsteren and coworkers [7,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Although the present study does not identify any other true minimum for the cis isomer, the experimental study on cis-stilbene in argon clusters 39 has observed an S 1 local minimum in the cis region. Furthermore, the semiempirical 37 and configuration interaction singles (CIS) 58,59 methods have identified a cis minimum. It is not surprising that dynamic correlation stabilizes the DHP minimum with respect to the cis minimum and/or lowers the barrier of DHP formation on the S 1 PES.…”
mentioning
confidence: 99%